A chemical tanker scheduling problem: Port of Houston case study. (11th October 2019) - Cankaya, Burak; Wari, Ezra; Tokgoz, Berna Eren
The objective of this study was to develop scheduling solutions for chemical vessels in a port. Chemical tankers carry multiple liquid cargos and have to visit multiple terminals to load/unload these cargos. The practice to date in scheduling these loading/unloading activities for the Port of Houston (PoH) has primarily involved manual methods, which result in several inefficiencies such as long waiting times and inefficient resource utilisation. This paper proposes three methods for tanker-scheduling problems, formulated as an open-shop scheduling problem with sequence-dependent post-set-up times: a mixed-integer programming (MIP); a constraint programming (CP); and a dispatching rule, longest processing time (LPT) scheduling heuristic. Overall, the results showed the MIP method to be a more suitable tool for hourly and daily scheduling, whereas the CP and the LPT heuristic proved suitable for longer-horizon scheduling problems (weekly, monthly, or semi-annual) and for use as real-time scheduling tools.